Construction and Implementation Path of Innovation and Entrepreneurship Practice Platform for Information Majors under the New Engineering Background - Lyu, Wenjing; Liang, Jian (International Journal of Social Sciences and Public Administration, 2025)
With the "New Engineering" concept, information education faces new challenges and opportunities, requiring the cultivation of innovative and entrepreneurial talents. Traditional teaching methods and practice platforms no longer meet the needs of modern information students. Therefore, building an innovation and entrepreneurship platform that aligns with New Engineering is crucial for educational reform. This research explores the construction, evaluation, and interdisciplinary integration of such platforms.Using literature analysis, case studies, and relevant methods, the study examines the current state and challenges of practice platforms in information education under New Engineering. The findings suggest the need for a project-driven, industry-university-research integrated platform, supported by a scientific evaluation system emphasizing interdisciplinary resource integration.This study provides a theoretical framework and practical approach for building innovation and entrepreneurship platforms in information education, offering new insights for reforming the field.